2012
DOI: 10.1038/leu.2012.182
|View full text |Cite
|
Sign up to set email alerts
|

The role of novel agents on the reversibility of renal impairment in newly diagnosed symptomatic patients with multiple myeloma

Abstract: The role of thalidomide, bortezomib and lenalidomide in multiple myeloma patients presenting with renal impairment was evaluated in 133 consecutive newly diagnosed patients who were treated with a novel agent-based regimen. A significant improvement of renal function (XrenalPR (renal partial response)) was observed in 77% of patients treated with bortezomib, in 55% with thalidomide and in 43% with lenalidomide (P ¼ 0.011). In multivariate analysis, bortezomib-based therapy was independently associated with a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(108 citation statements)
references
References 42 publications
7
99
0
2
Order By: Relevance
“…The role of the novel agents thalidomide, bortezomib and lenalidomide in the management of MM patients presenting with RI was recently evaluated [23]. A significant improvement in renal function (PR renal ) was observed in 77, 55, and 43% of patients treated with bortezomib, thalidomide and lenalidomide, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the novel agents thalidomide, bortezomib and lenalidomide in the management of MM patients presenting with RI was recently evaluated [23]. A significant improvement in renal function (PR renal ) was observed in 77, 55, and 43% of patients treated with bortezomib, thalidomide and lenalidomide, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the analysis of a cohort of patients with glomerular filtration rate <50 mL/min entering the VISTA trial revealed 44% of renal responses in the VMP arm vs. 34% in the MP arm [25]. Many other series demonstrated partial or complete reversal of renal impairment with bortezomib or bortezomibcontaining regimens [26][27][28][29][30]. Retrospective data are also available demonstrating reversibility of RI in regimens containing immunomodulatory drugs [31].…”
Section: Do Institute Prompt Systemic Therapymentioning
confidence: 99%
“…[11][12][13][14][15]20 In particular, bortezomib plays a critical role in the management of patients with genetically high-risk MM 14,[21][22][23] and patients with renal insufficiency. 24,25 The introduction of subcutaneous administration has improved convenience compared with the intravenous approach and substantially reduced the risk of peripheral neuropathy (PN), 26 a major limiting factor for long-term administration. 27 Other studies have shown that once-weekly administration of bortezomib can significantly reduce the risk of PN while preserving efficacy.…”
Section: Introductionmentioning
confidence: 99%